Transcriptome-Wide Identification, Classification, and Characterization of AP2/ERF Family Genes in the Desert Moss Syntrichia caninervis - Li, Xiaoshuang; Zhang, Daoyuan; Gao, Bei; Liang, Yuqing; Yang, Honglan; Wang, Yucheng; Wood, Andrew J. (Frontiers in Plant Science, 2017)
AP2/ERF is a large family of plant transcription factors, which play important roles in the control of plant metabolism, development as well as responses to various biotic and abiotic stresses. The desert moss Syntrichia caninervis, due to its robust and comprehensive stress tolerance, is a promising organism for the identification of stress-related genes. Using S. caninervis transcriptome data, eighty AP2/ERF unigenes were identified by HMM modeling and BLASTP searching. Based on the number of AP2 domains, multiple sequence alignment, motif analysis and gene trees construction, ScAP2/ERF genes were classified into three main subfamilies (including 5 AP2 gene members, 72 ERF gene members and 1 RAV member) and 2 soloist members. We found that the ratio for each subfamily was constant between S. caninervis and the model moss Physcomitrella patens, however as compared to the angiosperm Arabidopsis, the percentage of ERF subfamily members in both moss species were greatly expanded, while the members of the AP2 and RAV subfamilies were reduced accordingly. The amino acids composition of AP2 domain of ScAP2/ERFs was very conservative compared with Arabidopsis. Interestingly, most of the identified DREB genes in S. caninervis belonged to A-5 group which play important roles in stress responses and are rarely reported in the literature. Expression profile analysis of ScDREB genes showed different gene expression patterns under dehydration and rehydration; the majority of ScDREB genes demonstrated a stronger response to dehydration relative to rehydration indicated that ScDREB may play an important role in dehydrated moss tissues. To our knowledge, this is the first study to detail the identification and characterization of AP2/ERF gene family in desert moss. Further, this study will lay the foundation for further functional analysis of these genes, provide greater insight to the stress tolerance mechanisms in S. carninervis. Additionally, it will provide a reference for AP2/ERF gene family classification in other moss species.